Economic Features Of Formation And Implementation Of State Migration Policy In Russia - Sergeevna Igonina, Angela (2019)
The effectiveness of the socio-economic system development of any modern state directly depends on the rational formation and effective implementation of the state migration policy. The purpose of the paper is to analyse the trends and problems of migration relations development in the Russian Federation, the specifics of the state migration policy and to develop recommendations for its improvement. The paper analyses the main elements of the regulatory framework regarding the regulation of the state migration policy in the Russian economy. The main approaches to the rational implementation of the state migration policy in relation to illegal migrants are highlighted. The dynamics of influence of migration inflows into the Russian Federation in 2010 - 2018 to crime rate is statistically evaluated. It is shown that from the point of view of maximizing the average level of profitability of products in the Russian economy, the annual flow of migrants of working age should be about 200-250 thousand people. Recommendations have been developed to improve the state migration policy in Russia.